Discordant monoamniotic twins with Pena–Shokeir phenotype. Issue 10 (18th August 2016) - Adam, Sumaiya; Lombaard, Hennie; Spencer, Careni
Key Clinical Message: Pena–Shokeir phenotype is a rare disorder. However, its etiology is incompletely understood. It may be familial or may be due to anoxic–ischemic etiology. Although rare, it can affect one twin in a monoamniotic pregnancy, most likely due to early cord entanglement. Abstract : Pena–Shokeir phenotype is a rare disorder. However, its etiology is incompletely understood. It may be familial or may be due to anoxic–ischemic etiology. Although rare, it can affect one twin in a monoamniotic pregnancy, most likely due to early cord entanglement.